Assessment of occupational exposure to pesticides in a pooled analysis of agricultural cohorts within the AGRICOH consortium. Issue 6 (23rd March 2016) - Brouwer, Maartje; Schinasi, Leah; Beane Freeman, Laura E; Baldi, Isabelle; Lebailly, Pierre; Ferro, Gilles; Nordby, Karl-Christian; Schüz, Joachim; Leon, Maria E; Kromhout, Hans
Abstract : Background: This paper describes methods developed to assess occupational exposure to pesticide active ingredients and chemical groups, harmonised across cohort studies included in the first AGRICOH pooling project, focused on the risk of lymph-haematological malignancies. Methods: Three prospective agricultural cohort studies were included: US Agricultural Health Study (AHS), French Agriculture and Cancer Study (AGRICAN) and Cancer in the Norwegian Agricultural Population (CNAP). Self-reported pesticide use was collected in AHS. Crop-exposure matrices (CEMs) were developed for AGRICAN and CNAP. We explored the potential impact of these differences in exposure assessment by comparing a CEM approach estimating exposure in AHS with self-reported pesticide use. Results: In AHS, 99% of participants were considered exposed to pesticides, 68% in AGRICAN and 63% in CNAP. For all cohorts combined (n=316 270), prevalence of exposure ranged from 19% to 59% for 14 chemical groups examined, and from 13% to 46% for 33 active ingredients. Exposures were highly correlated within AGRICAN and CNAP where CEMs were applied; they were less correlated in AHS. Poor agreement was found between self-reported pesticide use and assigned exposure in AHS using a CEM approach resembling the assessment for AGRICAN (κ −0.00 to 0.33) and CNAP (κ −0.01 to 0.14). Conclusions: We developed country-specific CEMs to assign occupational exposure to pesticides in cohorts lacking self-reported data on the use of specific pesticides. The different exposure assessment methods applied may overestimate or underestimate actual exposure prevalence, and additional work is needed to better estimate how far the exposure estimates deviate from reality.